2020
DOI: 10.1111/nph.16391
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional relationships between plasmodesmata and plant endoplasmic reticulum–plasma membrane contact sites consisting of three synaptotagmins

Abstract: Summary Synaptotagmin 1 (SYT1) has been recognised as a tethering factor of plant endoplasmic reticulum (ER)–plasma membrane (PM) contact sites (EPCSs) and partially localises to around plasmodesmata (PD). However, other components of EPCSs associated with SYT1 and functional links between the EPCSs and PD have not been identified. We explored interactors of SYT1 by immunoprecipitation and mass analysis. The dynamics, morphology and spatial arrangement of the ER in Arabidopsis mutants lacking the EPCS compon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
86
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(89 citation statements)
references
References 45 publications
3
86
0
Order By: Relevance
“…In this study, we corroborate a recent report describing the establishment of a putative tethering complex between the synaptotagmins 1 and 5, and the Ca 2+ -dependent lipid binding protein CLB1/SYT7 (hereafter CLB1) at EPCSs ( Ishikawa et al , 2020 ), and we expand their analysis by showing that SYT1 and SYT5 can form homo- and heterodimers in vivo . We also show that changes in extracellular Ca 2+ have a limited effect in EPCS organization with the exception of treatments with salts of the rare earth elements (REEs) lanthanum (La 3+ ) and gadolinium (Gd 3+ ).…”
Section: Introductionsupporting
confidence: 90%
See 2 more Smart Citations
“…In this study, we corroborate a recent report describing the establishment of a putative tethering complex between the synaptotagmins 1 and 5, and the Ca 2+ -dependent lipid binding protein CLB1/SYT7 (hereafter CLB1) at EPCSs ( Ishikawa et al , 2020 ), and we expand their analysis by showing that SYT1 and SYT5 can form homo- and heterodimers in vivo . We also show that changes in extracellular Ca 2+ have a limited effect in EPCS organization with the exception of treatments with salts of the rare earth elements (REEs) lanthanum (La 3+ ) and gadolinium (Gd 3+ ).…”
Section: Introductionsupporting
confidence: 90%
“…ER–mitochondria and ER–plastid contact sites; Xu et al , 2008 ; Block and Jouhet, 2015 ; Fan et al , 2015 ; Michaud et al , 2016 ), intercellular communication (e.g. plasmodesmata; Uchiyama et al , 2014 ; Levy et al , 2015 ; Tilsner et al , 2016 ; Ishikawa et al , 2020 ), organelle distribution (e.g. ER–peroxisome, ER–plastid, and ER–Golgi contact sites; Andersson et al , 2007 ; Sparkes et al , 2009 ; Barton et al , 2013 ), and the Ca 2+ -dependent regulation of stress responses [ER–plasma membrane (PM) contact sites (EPCSs); Schapire et al , 2008 ; Yamazaki et al , 2008 ; P. Wang et al, 2014 , 2016 ; Pérez-Sancho et al , 2015 ; Kim et al , 2016 ; Lee et al , 2019 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The association between viral MPs and SYTA/1 was studied in detail. SYTA/1 was found to be required for the movement of viruses from the Tobamovirus [TMV, TVCV, and Youcai mosaic virus (YoMV) (Uchiyama et al, 2014;Cabanillas et al, 2018;Ishikawa et al, 2020). SYTA/1 forms a complex with SYTE/5 and SYT7 that likely also involves actin (Ishikawa et al, 2020), and was shown to localize at PD entrances (Levy et al, 2015;Ishikawa et al, 2020).…”
Section: Mcs and Viral Movementmentioning
confidence: 99%
“…Analysis of cellular factors involved in interactions with MP PLS revealed its ability to bind plant synaptotagmin A (SYTA) (Yuan et al, 2018). SYTA is localized to the plasma membrane (PM), concentrated around Pd and recognized as a tethering factor of ER-PM contact sites (Uchiyama et al, 2014;Levy et al, 2015;Yuan et al, 2018;Ishikawa et al, 2020;Liu et al, 2020).…”
Section: Does the Plasmodesmal Localization Signal (Pls) Direct Mp Tomentioning
confidence: 99%